Analysis the Impact of Dynamic Capability on Firm Performance with mediation variables of Agility in Batam’s Manufacturing Industry. - Agustinus Setyawan; Hermanto Hermanto (YUME : Journal of Management, 2022)
AbstractTechnological developments increasingly make the competition between companies more intensity. Manufacturing industry is a sector that give the most contribution to national economy. In improving organizational performance, dynamic capabilities role has recognized and desired by all companies. But mostly the companies believe that dynamic capability is built on only the side of Human Resource and the very complicated creation process.This study uses a quantitative approach in analyzing and presenting data from the results of research data. The object of research used in this study are 150 employees who work in the manufacturing industry in Batam. The data collected from the respondents will be processed using the SmartPLS 3 and SPSS systems.The research was carried out with the aim of knowing the effect of the components of the company''s performance, namely Human Resource Management, Intellectual Capital, Dynamic Capability on company performance on employees of the manufacturing industry in Batam City. Research Result Shows That Human resource management has a negative influence on Dynamic Capability, Intellectual capital has an effect on Dynamic Capability, Agility as mediation variable has a significant effect through Dynamic Capability and Firm Performance, and Dynamic capability has a positive influence on firm performance. Keywords: Human Resource Management, Intellectual Capital, Dynamic Capability, Agility, Firm Performance